Teaching in the Immersive Era: Professors’ Perspectives on XR in Higher Education - Otemaier, Rafaela; Albuquerque, Regina; Falabretti, Ericson Savio; Reinehr, Sheila; Malucelli, Andreia (Proceedings of the ACM International Conference on Interactive Media Experiences Workshops (IMXw); 2025: Proceedings of the ACM International Conference on Interactive Media Experiences Workshops, 2025)
The increasing presence of digital natives in higher education has intensified the demand for innovative teaching methodologies that enhance student engagement and learning outcomes. In this context, Extended Reality (XR), encompassing Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR), has gained traction as a means to create immersive environments that support experiential learning. This study aims to analyze professors’ perceptions regarding the adoption, benefits and challenges of immersive technologies in higher education. A survey was conducted with 40 professors who have recently started using these technologies in their classes. The results reveal that immersive environments enhance student engagement, comprehension, and interaction. However, challenges such as limited infrastructure, insufficient technical knowledge, and content adaptation were identified as barriers to adoption. Despite these challenges, 94.1% of respondents expressed their intention to continue using immersive technologies. The findings suggest that addressing these obstacles through targeted support and training could improve the integration of XR tools, thereby increasing their effectiveness for educational purposes.